Maladies of Empire How colonialism, slavery, and war transformed medicine - Downs, Jim 1973- (The Belknap Press of Harvard University Press, 2021)
"Standard histories of medicine celebrate brilliant Westerners such as Florence Nightingale and John Snow. In this unorthodox telling, Jim Downs turns our focus to another key group of contributors: the subjugated peoples-forced into close quarters by enslavement and empire-whose bodies were the experimental matter on which medical progress relied"--